Pengaruh Integrated Marketing dan Relationship Marketing Terhadap Loyalitas Pelanggan - Sekar Widyastuti Pratiwi; Suparwan CK; Nursery Alfaridi (Institut Transportasi dan Logistik Trisakti, 2019)
The purpose of the research is to analyze and find out the effect of integrated marketing and marketing relationship to the airlines customers’ loyalty using Structural Equation Modelling (SEM). The population of the research was airlines passengers of Soekarno Hatta Airport and sample was taken of 105 respondents. The data was collected using questionnaire, interview, documented study, studied variables by using Likert Scale. The questionnaire result was analyzed using Lisrel (statistics software). The result from hypothesis test is parsially the integrated marketing variable does not show significant effect to loyalty variable that can be seen from the score t = -0.99 < -1.96. Based on t score t = 8.27 > 1.96, relationship marketing is the variable that give strong and significant effect to loyalty variable. Simultaneously, independent variables, relationship marketing dan integrated marketing, give positive and significant effect to loyalty variable. Based on 11 criteria of GOF / Good on Fit model, the model in this research has shown good modeling which means the measurement model obtained from the data is in accordance with the research hypothesis due to 8 out of 11 criteria fullfilled